Effects of visual roll on steering control and gaze behavior in a motorcycle simulator. (April 2016) - Lobjois, Régis; Siegler, Isabelle Anne; Mars, Franck
Highlights: We examined the effects of visual roll on gaze and riding behavior in a motorcycle simulator. In the no-roll condition, results were compatible with a steer where you look behavior. In the roll conditions, the visual behavior was shifted on the vertical direction. More fixations were directed further ahead down the road. This led to a degradation in steering stability and an offset in lateral positioning. Abstract: The goal of this study was to examine the effects of visual roll tilt on gaze and riding behavior when negotiating a bend using a motorcycle simulator. To this end, experienced motorcyclists rode along a track with a series of right and left turns whilst the degree of visual roll tilt was manipulated in three different conditions. Gaze behavior was analyzed by using the tangent point as a dynamic spatial reference; the deviation of gaze to this particular point was computed in both the horizontal and vertical directions. Steering control was assessed in terms of the lateral positioning, steering stability and number of lane departures. In the no-roll condition, the motorcyclists tracked a steering point on the road ahead, which was compatible with the hypothesis of "steer where you look" behavior. In the roll condition, our results revealed that the horizontal distribution of gaze points relative to the tangent point was preserved. However, significantly more fixations were made further ahead of the tangent point in the vertical direction. This modification of visual behavior was coupled with a degradation in steering stability and an offset in lateral positioning, which sometimes led to lane departures. These results are discussed with regard to models of visual control of steering for bend negotiation.